In Vitro Biocompatibility of Electrospun Chitosan/Collagen Scaffold. (19th September 2013) - Wang, Peiwei; Liu, Junli; Zhang, Teng
Abstract : Chitosan/collagen composite nanofibrous scaffold has been greatly concerned in recent years for its favorable physicochemical properties which mimic the native extracellular matrix (ECM) both morphologically and chemically. In a previous study, we had successfully fabricated nanofibrous chitosan/collagen composite by electrospinning. In the present study, we further investigate the biocompatibility of such chitosan/collagen composite nanofiber to be used as scaffolds in vascular tissue engineering. The porcine iliac artery endothelial cells (PIECs) were employed for morphogenesis, attachment, proliferation, and phenotypic studies. Four characteristic EC markers, including two types of cell adhesion molecules, one proliferation molecule (PCNA), and one function molecule (p53), were studied by semiquantitative RT-PCR. Results showed that the chitosan/collagen composite nanofibrous scaffold could enhance the attachment, spreading, and proliferation of PIECs and preserve the EC phenotype. Our work provides profound proofs for the applicable potency of scaffolds made from chitosan/collagen composite nanofiber to be used in vascular tissue engineering.